The Influence of Meaningful Work and Work Motivation on Performance with Organizational Commitment as an Intervening Variable - Laili, Nihayah Rohmatul; Iramani, Iramani; Yulianti, Emma (JURNAL MANAJEMEN MOTIVASI, 2025)
This study aims to examine the effect of meaningful work and work motivation on employee performance, as well as the mediating role of organizational commitment in this relationship. Adopting a quantitative approach, the research population consisted of 382 employees from public health centers (Puskesmas) in the Central Surabaya Region. A sample size of 195 respondents was selected, with data collected using a Likert scale questionnaire. Data analysis was performed using descriptive inferential analysis and path analysis via PLS-SEM with SmartPLS 4 software to test seven hypotheses. The results indicate that meaningful work significantly and positively influences both employee performance and organizational commitment. Similarly, work motivation has a significant positive effect on organizational commitment and employee performance. However, organizational commitment itself does not have a significant effect on employee performance. Furthermore, organizational commitment, when acting as a mediating variable between meaningful work or work motivation and employee performance, was found to have an insignificant effect. Keywords: Meaningful work; Work motivation; Performance; Commitment